STUDI PERILAKU ADAPTASI MANUSIA TERHADAP LINGKUNGAN SOSIAL DALAM PENAMBAHAN FUNGSI RUANG KOMERSIAL HUNIAN TRADISIONAL BALI DI UBUD - ERWIN ARDIANTO HALIM (Serat Rupa: Journal of Design, 2016)
Tourism in Bali has significant effect to Balinese social aspect.  It can be seen from the Balinese people daily behavior that has changed from traditional society to modern and diverse society.  The conviction to conserve traditional pattern of life and behavior is still exists in the Balinese society and their posterity, but in the other side, tourism development and economical urgency creates difficult situation to conserve the purity of Balinese cultural tradition.  This situations influence Balinese cultural products created nowadays, such as architectural spaces that represent the people within.  The changes occurring in traditional Balinese houses happened mostly in concentrated tourism areas, such as Ubud.  In the government urban development plan, Ubud is selected as one of strategic tourism point of interest that is cultural tourism.  Consequently, Ubud also functions as strategic economic income resource for Bali.  The changes in traditional Balinese houses mostly happened because of the need to adapt with socio-cultural context, where local tourists and expatriates come and even stay for longer time.  To accommodate tourist’s needs, Ubud villagers set off to open restaurants, cafes, art galleries, souvenir shops, and travel agents in their houses.  These commercial areas are located in their traditional houses, with modification of rooms or even addition of rooms with other functions.  This research focused on the space transformation to commercial spaces in traditional Balinese houses.  There are abundant philosophical values that have to be conserve in traditional Balinese houses between generations.  Those philosophical values have sacred meanings within its design elements, such as building orientation, building elevation, facades, borders and zoning.  With the addition of commercial places, how do The Ubud people managed to continue their tradition and the values within? Therefore, the main problem that is being researched here is about the collision between the need to adapt to socio-cultural context in the society and the need to conserved cultural traditions in the family and their sacred meanings.   Keywords: human adaptative behaviour; space transformation; traditional house; Ubud